Solve: 2(x-3) - 3(x+5) = 3(x-2) - 7
First: eliminate parenthesis --- distribute the outer terms with the terms in parenthesis....
2(x)+2(-3)-3(x)-3(5)=3(x)+3(-2)-7
*Combine the terms...
2x - 6 - 3x - 15 = 3x - 6 - 7
2x - 3x - 6 - 15 = 3x - 6 - 7
- x - 21 = 3x - 13
Sec: add "21" by both sides...
- x - 21 + 21 = 3x - 13 + 21
- x = 3x + 8
*Subtract "3x" from both sides...
- x - 3x = 3x - 3x + 8
- 4x = 8
Third: isolate "x" on one side --- divide both terms by "-4"...
- 4x/-4 = 8/-4
x = -8/4
x = -2
*Check/Prove the Solution: Replace "-2" with the x-variables in the equation...
2(-2-3) - 3(-2+5) = 3(-2-2) - 7
2(-5) - 3(3) = 3(- 4) - 7
- 10 - 9 = - 12 - 7
- 19 = - 19
True
2007-02-06 05:46:39
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
5(3x + 2) - 3(2x - 7) 15x + 10 -6x +21 9x - 11 15-2(x + 1) = 3x + 7 15 -2x -2 = 3x + 7 13 - 5x = 7 -5 x = -6 x = 6/5 The median of a group of numbers is that number in which half of the values are greater than the median and half are less than the median. In this case you have an even amount of numbers so the median here is (60 + 50) /2 or 55. 2y = x = 8 2y = x y = x/2 or y = 4 (3x-2) 2 = 6x - 4
2016-05-24 00:02:37
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2(x - 3) - 3(x + 5) = 3(x - 2) - 7
2x - 6 - (3x + 15) = 3x - 6 - 7
2x - 6 - 3x - 15 = 3x - 13
-x - 21 = 3x - 13
- x - 21 + x = 3x - 13 + x
- 21 = 4x - 13
- 21 + 13 = 4x - 13 + 13
- 8 = 4x
- 8/4 = 4x/4
- 8/4 = x
- 2 = x
The answer x = - 2
Insert the x value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
2(x - 3) - 3(x + 5) = 3(x - 2) - 7
2(- 2 -3) - 3(- 2 + 5) = 3(- 2 - 2) - 7
2(- 5) - 3(3) = 3(-4) - 7
- 10 - 9 = - 12 - 7
- 19 = - 19
- - - - - - - - - - - - - -s-
2007-02-06 06:52:10
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
0⤋
you are missing a right parentheses on the LHS of this equation, so i'll include it for you....
Equation becomes 2x-6-3x-15=3x-6-7
=>gathering both set of coefficients together on either side of the equals sign gives -8=4x=> x=-2
Proving it by putting back into the equation gives 2(-5)-3(3)=3(-4)-7
=>-19=-19 QED
2007-02-06 05:43:58
·
answer #4
·
answered by RobLough 3
·
0⤊
0⤋
2x - 6 - 3x - 15 = 3x - 6 - 7
2x - 3x - 3x = - 6 - 7 + 15 + 6
- 4x = 8
x = - 2
Check
LHS = 2(-2-3) - 3(-2 + 5) = -10 - 9 = -19
RHS = 3(-2 - 2) - 7 = -12 - 7 = -19
2007-02-06 05:58:33
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
x=4
2007-02-06 05:44:14
·
answer #6
·
answered by Char 7
·
0⤊
2⤋
x=-2
Checking the work:
2(x-3)-3(x+5=3(x-2)-7
2(-2-3)-3(-2+5)=3(-2-2)-7
2(-5)-3(3)=3(-4)-7
-10-9=-12-7
-19=-19
2007-02-06 05:58:04
·
answer #7
·
answered by Saphira 3
·
0⤊
0⤋
first you foil it: (2x-6)-(3x+15)=(3x-6)-7
then combine like terms: -x-9=3x-13
get variables on one side: 4=4x
get x by itself: 1=x
And to prove it just plug the value for x which is 1 into the original equation
2007-02-06 05:50:16
·
answer #8
·
answered by idon'tknowanymore 2
·
0⤊
0⤋
2x-6-3x-15=3x-6-7
-x-21=3x-13
-x-3x-21=3x-3x-13
-4x-21=-13
-4x-21+21=-13+21
-4x=8
-4x/-4=8/-4
x=-2
2007-02-06 06:15:02
·
answer #9
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
-19 is answer.
2007-02-06 05:48:15
·
answer #10
·
answered by mail_jenil 1
·
0⤊
1⤋